EXPLORING THE FRONTIERS OF WORKING MEMORY: AN INTEGRATIVE REVIEW - Faria, Sônia; Salles, Débora; Pereira, Liliane Desgualdo (ARACÊ, 2025)
Working memory refer to the processes of information maintenance and executive control necessary for planning and performing tasks such as reasoning, comprehension, and learning. Understanding how this type of memory works and its relationship with auditory skills can contribute to rehabilitation of individuals with learning difficulties. The present study was conducted by searching for published works available in the databases PubMed, NCBI, MEDLINE, Scielo, and Google Scholar, with useful information for explanation and understanding of the topic. Among the studies selected for the present review, there are notable and inspiring research and discoveries. Over the years, the topic has been widely studied and researched, including its relation to childhood, the brain, and the biochemical and molecular processes that occur within it, as well as the adjacent auditory and phonological repercussions. Considering the importance of working memory in academic performance, it is essential to use available tests in students, aiming to expand the range of strategies that can improve their conditions and study capabilities. Further studies in this direction are needed in the educational context to guide the next steps of educational professionals and the future of students.